DIALOGUE ON INNOVATIVE PEDAGOGY AND PARTNERSHIP IN EDUCATION: INTERACTIVE CONTENT FOR ONLINE IMPROVEMENT OF THE QUALIFICATIONS OF TEACHERS - Skrypnik , Marina; Kravchynska , Tetiana; Volynets , Nataliia (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
Through the analysis of the concept of dialogue (Socratic and postmodern understanding), interactive educational content for online dialogue with students of advanced training courses on the issue of innovative pedagogy and partnership in education is revealed. The author’s approaches to the development of a workbook in two formats are substantiated, a comparison of paper and electronic editions is made, educational and educational-creative tasks in the workbook are structured. The potential of online programs and tools for creating educational content for the course is revealed.